DAMPAK MANAJEMEN LABA TERHADAP ALOKASI INVESTASI PERUSAHAAN - Siti Rokhaniyah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This study examines the earnings management affect the allocation of investment, the manufacturing companies listed on the Indonesia Stock Exchange, in the period 2009 – 2013. Allocation of investment, as the dependent variable, proxies by investment in fixed assets (net property, plan, and equipment), and the independent variables, earnings management is proxies by discretionary accruals that calculated following the model of Jones modification. This is because this model is the best model (Dechow, et al, 2002) as separate components of discretionary accruals and non-discretionary accruals. To obtain more accurate results we use several control variables, including fixed asset investment of the previous period, investment opportunity, asset growth, and net operating cash flow. The results showed that earnings management, both this period (t) and the previous period (t-1) has positive significant effect on the allocation of investment companies. That is that the higher the earnings management (DA), the allocation of investment companies will be higher, and there is a tendency companies to invest in excess (over-investment). Therefore, we need a certain mechanism that can affect managers in making investment decisions more efficiently. Equity-based compensation can anticipate the negative effect. With the equity-based compensation, earnings management is suspected influence on the allocation of investment is not significant. Keywords: allocation of investment, earnings management, discretionary accrual